2006
DOI: 10.1088/0957-4484/17/5/026
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of zigzag single walled carbon nanotubes

Abstract: Carbon nanotubes (CNTs) are known to possess extraordinary strength, stiffness and ductility properties. Their fracture resistance is an important issue from the perspective of durability and reliability of CNT-based materials and devices. According to existing studies, brittle fracture is one of the important failure modes of Single-Walled Carbon Nanotube (SWNT) failure due to mechanical loading. However, based on the authors' knowledge, the fracture resistance of CNTs has not been quantified so far. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Table 2 summarizes the key mechanical parameters compared with those of typical 1D and 2D nanostructures such as carbon nanotubes and TMD monolayers. Note that the Young’s modulus and breaking strength of the present M 6 X 6 atomic wires even approach two-thirds of those of single-wall carbon nanotubes ( Y ∼ 1 TPa, σ ∼ 95 GPa), 49 which is known as the strongest and stiffest 1D material. On the other hand, 2D TMDs have relatively lower Young’s modulus, i.e.…”
Section: Resultsmentioning
confidence: 78%
“…Table 2 summarizes the key mechanical parameters compared with those of typical 1D and 2D nanostructures such as carbon nanotubes and TMD monolayers. Note that the Young’s modulus and breaking strength of the present M 6 X 6 atomic wires even approach two-thirds of those of single-wall carbon nanotubes ( Y ∼ 1 TPa, σ ∼ 95 GPa), 49 which is known as the strongest and stiffest 1D material. On the other hand, 2D TMDs have relatively lower Young’s modulus, i.e.…”
Section: Resultsmentioning
confidence: 78%
“…Influence of CNT embedded length L CNT and CNT radius R CNT on the specific pullout energy. [45] also showed that the longer nanotubes have a higher fracture resistance than the shorter tubes and the fracture energy is not much dependent on the diameter of the CNTs. In the experimental study of Mirjalili and Hubert [12], it was also concluded that the fracture toughness can be improved by increasing the length of CNTs.…”
Section: Bridging Effect Of Cnt In Cnt Pulloutmentioning
confidence: 92%
“…The method used in this study is based on the displacement-controlled test which is commonly used for macroscale fracture specimens [45] and the kinetic energy is neglected. According to Fig.…”
Section: Bridging Effect Of Cnt In Cnt Pulloutmentioning
confidence: 99%
“…Further analyses have shown that brittle fracture in zig-zag SWCNT is the consequence of breaking atomic bonds between the carbon atoms in a short period of time. However, longer nanotubes could exhibit higher fracture resistance when they are compared to shorter tubes [25].…”
Section: The Effect Of Structural Parameters On the Properties Of Zig-zag And Armchair Carbon Nanotubesmentioning
confidence: 99%